Manajemen Pengelolaan Sampah Studi Kasus di Bank Sampah Tirtarona Tlogomas Kota Malang - Yulianti, Yulianti; Huda, Rofi'ul (Direktorat Penelitian dan Pengabdian kepada Masyarakat (DPPM), 2018)
BSM assists the Malang City Government in fostering, training and assisting the people of Malang City who are incorporated in BSM customers in 3R (Reuse, Reduse, Recycle) waste management from household sources. The BSM unit was established which was strengthened from the SK of the Central BSM in Malang, and not the personal owner or RT / RW. The issues that are prioritized in the PKM (community partnership program) activities are the target audience of economically unproductive community partners, namely the BST (Waste Bank Tirtarona) and BSM (Community Waste Bank) partners. The two partners whose initial existence was productive but which are still not optimal and have not been utilized according to the objectives of BSM. The purpose of the community waste management partnership program in the kecamatan area. lowokwaru Malang City to optimize waste management productivity according to the purpose of the establishment of the Waste Bank organization in creating peace, and comfort in community life. Specific targets to be achieved empower RT / RW waste managers as partners of Malang City BSM in managing / managing waste independently. Starting from receiving garbage, sorting, administering, weighing, processing up to the reporting stage as a form of BSM organizational evaluation to be able to contribute to its environment. The method used is the dissemination of the benefits of BSM waste management, activating the BSM work program by inviting the management with training and mentoring activities, comparative studies, helping waste production equipment and assisting in the renovation of BSM buildings. The results of the implementation of the community partnership program were found; 1). BSM Unit management model that is centralized, meaning that all activities are still based on the RT / RW chairman's instructions in the local environment. The Chairperson of BSM works on the recommendation of the chairman of the PKK RW driving team where the land is established by BSM. 2) the condition of the human resources of the majority BSM management from the age of 60 and above, thus influencing the performance in carrying out the BSM work program. 3). BSM community conditions are in urban areas whose activities are busy working, so that they often become obstacles for the organizers to carry out social activities.